Hibah Wasiat Atas Tanah Bekas Adat Berdasarkan Akta Hibah Wasiat Yang Dibuat Oleh Camat - Andi Ainun Magfirah Ramadhani; Muhammad Basri; Muhammad Ilham Arisaputra (Universitas Widya Gama Malang, 2022)
A testamentary grant on ex-customary land as an object of the dispute by looking at the Court's Decision which decided on a civil dispute case Number: 21/Pdt.G/2015/PN/BLK which in its decision rejected the plaintiff's claim that the ex-customary land belonged to him, because the defendant has proof of ownership, namely a will grant deed carried out by the Camat as PPATS. This study aims to analyze the strength of the proof of the will as the basis for land tenure and ownership, as well as to analyze the validity of ownership and control of ex-customary land rights based on the testament grant deed made by the sub-district head as PPATS. This study uses empirical research methods, by analyzing the data collected through interviews and literature study, then the collected data is analyzed using descriptive analysis techniques. The results of this study indicate that the testament grant deed in the case of the Civil dispute Number 21/Pdt.G/2015/PN/BLK does not have a basis of manufacture where the will grant deed does not have a certificate and is only made in front of the sub-district head as PPATS, further should have been canceled by the Bulukumba District Court because it was not following the procedure for making a will and the beneficiary did not get his rights. So that it does not have the validity of ownership and control of rights if it is based on a will grant deed made by the sub-district head as PPATS